IMPROVEMENT OF METHODOLOGY OF TEACHING ANALYTICAL CHEMISTRY BASED ON MODERN INFORMATION AND PEDAGOGICAL TECHNOLOGIES - Gulzor Islambaevna Sapaeva; Urunbayeva Akmerzhan Allamurat qizi (Bright Mind Publishing, 2025)
Learning is carried out at different stages, at which the student understands the content of education and understands what his cognitive tasks are. Processes such as intuition, perception and imagination take an active part in this. At the next stage, they understand the educational material, understand its essence and generalize it. As a result, they gain new knowledge. To do this, they use analysis, synthesis, comparison, and conclusion. At the last stage, new knowledge is consolidated through exercises, independent work, and additional comments from the teacher.
Keywords: Teacher, analysis, synthesis, comparison, conclusion, technology, multimedia, education, computer, innovation, methodology.